2001
DOI: 10.2116/analsci.17.1453
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recognition of Endocrine Disruptors by Fluorogenic γ-Cyclodextrin Having Pyrene-Tosyl Substituents on Hetero Rims

Abstract: Cyclodextrins (CyDs) have attracted interest as an enzyme model or supramolecular compounds, because they can accommodate with a variety of guests, such as organic molecules or metals, in their cavities in an aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A newly developed near-field focusing plate was used for this measurement. The operation of the NFIR microscope was performed as described previously (24). The distance separating the sample and the probe was regulated by the uncontacted physical force interaction between the sample and the probe, and this distance was maintained at ϳ30 nm.…”
Section: Methodsmentioning
confidence: 99%
“…A newly developed near-field focusing plate was used for this measurement. The operation of the NFIR microscope was performed as described previously (24). The distance separating the sample and the probe was regulated by the uncontacted physical force interaction between the sample and the probe, and this distance was maintained at ϳ30 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The operation of NFIR was performed as described in the literature. 4 The distance separating the sample and probe was regulated by an uncontacted physical force interaction between the sample and the probe, 5 and was maintained at approximately 30 nm. The probe tip oscillated parallel to the sample surface.…”
mentioning
confidence: 99%
“…The system was described in detail in a previous paper. 25) The diameter of the tip of the probe was less than 1 mm. The distance separating the sample and probe was regulated by uncontacted physical force interaction and maintained at approximately 30 nm.…”
Section: Measurementsmentioning
confidence: 99%
“…We did not study the penetration depth of IR light into the film. However, it was reported that a near field depends on the radius of the tip of the diffraction-type probe; 25) therefore, the penetration depth was estimated to be around 1 mm. The effect of film thickness on the resolution of the recording spots will be studied in the future.…”
Section: Photochromic Recording and Nondestructive Readout Using Near...mentioning
confidence: 99%